2014
DOI: 10.1371/journal.pone.0091282
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic Acid Controls Allergic and Inflammatory Responses in Experimental Allergic Conjunctivitis

Abstract: Pollen is the most common aeroallergen to cause seasonal conjunctivitis. The result of allergen exposure is a strong Th2-mediated response along with conjunctival mast cell degranulation and eosinophilic infiltration. Oleanolic acid (OA) is natural a triterpene that displays strong anti-inflammatory and immunomodulatory properties being an active anti-allergic molecule on hypersensitivity reaction models. However, its effect on inflammatory ocular disorders including conjunctivits, has not yet been addressed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
(34 reference statements)
0
25
0
1
Order By: Relevance
“…7). to have antiallergic properties [3] as well as being useful when uploaded onto nanoplatforms in anti-inflammatory applications [1]. In our study we showed that, in principle, only oleanolic acid at concentrations lower than 50 µM is not toxic for human corneal epithelial cells.…”
Section: Oa and Ua Impact On Production Of Metalloproteinases (Mmp-2 mentioning
confidence: 53%
See 1 more Smart Citation
“…7). to have antiallergic properties [3] as well as being useful when uploaded onto nanoplatforms in anti-inflammatory applications [1]. In our study we showed that, in principle, only oleanolic acid at concentrations lower than 50 µM is not toxic for human corneal epithelial cells.…”
Section: Oa and Ua Impact On Production Of Metalloproteinases (Mmp-2 mentioning
confidence: 53%
“…These compounds exert many biological activities such as anti-inflammatory, anticancer, antioxidant, and antiallergic [1,2]. In view of a wide variety of activities, they were also considered as suitable in ophthalmology in order to protect the eye surface against adverse effects of particular inflammations and allergies [1,3]. Some of the factors acting adversely may include matrix metalloproteinases (MMPs) or high levels of nitric oxide (NO).…”
Section: Introductionmentioning
confidence: 99%
“…This disease encompasses a diversity of pathological conditions and fundamental immunopathological mechanisms. Therefore, AC can be subdivided into seasonal and perennial allergic conjunctivitis . Previous data suggest that 15%–40% of the population world‐wide are affected by AC .…”
Section: Role Of Il‐1β In Allergic Conjunctivitis (Ac)mentioning
confidence: 99%
“…The current agents used for AC treatments include antihistamines, mast cell stabilizers, nonsteroidal anti-inflammatory drugs, and topical corticosteroids. 23,24 These agents are known to cause side effects after long-term use. As such, further research is mandatory for development of better treatment regimens.…”
mentioning
confidence: 99%